Multibeam bathymetry processed data (EM12 S-120 echosounder working area dataset) of RV HESPERIDES during cruise BIG95, Eivissa Channel, Mediterranean Sea - Miquel Canals; Galderic Lastras; Thore Falk Sager (PANGAEA, 2024)
Multibeam bathymetry data were collected during the BIG extquotesingle95 cruise in 1995 with the Spanish research vessel BIO Hespérides using a SIMRAD EM-12S (13 kHz, 81 beams). The data were processed using SwathEd software to a 50x50 m grid. The data is fully processed from raw files, which are available upon request. The data is projected to UTM WGS 1984 31N.